1996
DOI: 10.1152/ajpendo.1996.270.5.e890
|View full text |Cite
|
Sign up to set email alerts
|

Glucose tolerance and insulin action in healthy centenarians

Abstract: Advancing age has been found to be associated with a decline in insulin action. Nevertheless, no study has been conducted in healthy centenarians. Our study investigates glucose tolerance and insulin action in centenarians. Fifty-two subjects were enrolled. The subjects were divided in three groups as follows: 1) adults (< 50 yr; n = 20);2) aged subjects (> 75 yr; n = 22); and 3) centenarians (> 100 yr; n = 14). Body composition was studied by bioimpedance analysis. In all subjects, an oral glucose tolerance t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
101
2
3

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(112 citation statements)
references
References 20 publications
6
101
2
3
Order By: Relevance
“…28,[84][85][86][87] And it is known that high insulin-sensitivity is a striking marker of centenarians, people who live more than 100 years. 88,89 Insulin sensitivity was strongly associated with longevity in mice. 51,90 It is reasonable to suggest that insulin-sensitivity is a marker of deactivated mTOR.…”
Section: Cr In Humans: Extension Of Life By Delaying Age-related Disementioning
confidence: 99%
“…28,[84][85][86][87] And it is known that high insulin-sensitivity is a striking marker of centenarians, people who live more than 100 years. 88,89 Insulin sensitivity was strongly associated with longevity in mice. 51,90 It is reasonable to suggest that insulin-sensitivity is a marker of deactivated mTOR.…”
Section: Cr In Humans: Extension Of Life By Delaying Age-related Disementioning
confidence: 99%
“…Intriguingly, there is increasing evidence that preservation of insulin action might be one of the common peculiarities of centenarians that help maintain health and function throughout their extremely long life. Paolisso et al were the first to report that glucose tolerance and insulin sensitivity are better preserved in healthy centenarians in comparison to elderly individuals over 75 years of age 33) . A series of crosssectional studies have reproducibly demonstrated that the prevalence of type 2 diabetes, which is closely associated with age-related insulin resistance, is very low among Finnish 34) , Italian 35) , and Japanese centenarians 36) .…”
Section: Human Data On the Adipose Tissue Phenotype In Centenariansmentioning
confidence: 99%
“…[38][39][40][41][42][43][44][45][46][47][48][49] In contrast, mice deficient for S6K1 are hypersensitive to insulin 50,51 and live longer 52 And insulin sensitivity is associated with longevity in mice 53,54 and humans. 55,56 mTOR-induced insulin resistance was documented in different conditions. For example, nutrients cause TORdependent insulin resistance in rodents and humans.…”
Section: Mtor and Diabetic Complicationsmentioning
confidence: 99%